An ancient F-type subdwarf from the halo crossing the Galactic plane - Scholz, R. -D.; Heber, Ulrich; Heuser, Christian; Ziegerer, Eva; Geier, Stephan; Niederhofer, F (Astronomy & Astrophysics, 2015)
Aims. We selected the bluest object, WISE J0725-2351, from Luhman's new high proper motion (HPM) survey based on observations with the Wide-field Infrared Survey Explorer (WISE) for spectroscopic follow-up observations. Our aim was to unravel the nature of this relatively bright (V similar to 12, J similar to 11) HPM star (mu = 267 mas/yr).Methods. We obtained low-and medium-resolution spectra with the European Southern Observatory (ESO) New Technology Telescope (NTT)/EFOSC2 and Very Large Telescope (VLT)/X-Shooter instruments, investigated the radial velocity and performed a quantitative spectral analysis that allowed us to determine physical parameters. The fit of the spectral energy distribution based on the available photometry to low-metallicity model spectra and the similarity of our target to a metal-poor benchmark star (HD 84937) allowed us to estimate the distance and space velocity.Results. As in the case of HD 84937, we classified WISE J0725-2351 as sdF5: or a metal-poor turnoff star with [Fe/H] = -2.0 +/- 0.2, T-eff = 6250 +/- 100 K, log g = 4.0 +/- 0.2, and a possible age of about 12 Gyr. At an estimated distance of more than 400 pc, its proper motion translates to a tangential velocity of more than 500 km s(-1). Together with its constant (on timescales of hours, days, and months) and large radial velocity (about +240 km s(-1)), the resulting Galactic restframe velocity is about 460 km s(-1), implying a bound retrograde orbit for this extreme halo object that currently crosses the Galactic plane at high speed.
Keywords: proper motions; stars: distances; stars: kinematics and dynamics; stars: Population II; subdwarfs; white dwarfs